Social Psychology, 11th Edition - Saul Kassin (Cengage Learning, 2020)
Kassin/Fein/Markus' SOCIAL PSYCHOLOGY, 11th Edition, brings chapter concepts to life through a unique emphasis on current events in sports, music, entertainment, technology, social media, business, world politics and more. Combining scholarship with real-world illustrations, it helps you understand the field of social psychology through engaging connections to everyday life. Integrating both classic and emerging research, the text delivers comprehensive coverage of social cognition and applications to law, business, and health and well-being. In addition, author Hazel Rose Markus, a respected researcher in the study of cultural psychology, integrates culture and diversity topics into every chapter. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.